2023
DOI: 10.1007/s00572-022-01099-w
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring epiphytic orchids have specialized mycorrhizal fungal niches that are also linked to ontogeny

Abstract: Mycorrhizal symbiosis has been related to the coexistence and community assembly of coexisting orchids in few studies despite their obligate dependence on mycorrhizal partners to establish and survive. In hyper-diverse environments like tropical rain forests, coexistence of epiphytic orchids may be facilitated through mycorrhizal fungal specialization. However, information on the role of orchid mycorrhizal fungi (OMF) in niche differentiation and coexistence of epiphytic orchids is still scarce. In this study,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…Extant epiphytic orchids primarily occur in closed-canopy rainforests with mainly angiosperm trees (Zotz, 2016;Fernández et al, 2023;Spicer and Woods, 2022); such angiosperm rainforests were estimated to have formed approximately 60 Ma (Carvalho et al, 2021) and then dramatically expanded near the PETM (56 Ma) (Jaramillo et al, 2010;Huurdeman et al, 2021). Additionally, previous time estimations showed that some angiosperm groups, for example, Fabaceae and Malvaceae, that contained dominant trees of modern rainforests rapidly diverged approximately at the same time (Cvetkovic et al, 2021;Benton et al, 2022).…”
Section: Interactions With Rainforests Might Have Promoted the Divers...mentioning
confidence: 99%
See 1 more Smart Citation
“…Extant epiphytic orchids primarily occur in closed-canopy rainforests with mainly angiosperm trees (Zotz, 2016;Fernández et al, 2023;Spicer and Woods, 2022); such angiosperm rainforests were estimated to have formed approximately 60 Ma (Carvalho et al, 2021) and then dramatically expanded near the PETM (56 Ma) (Jaramillo et al, 2010;Huurdeman et al, 2021). Additionally, previous time estimations showed that some angiosperm groups, for example, Fabaceae and Malvaceae, that contained dominant trees of modern rainforests rapidly diverged approximately at the same time (Cvetkovic et al, 2021;Benton et al, 2022).…”
Section: Interactions With Rainforests Might Have Promoted the Divers...mentioning
confidence: 99%
“…Orchidaceae are crucial ecologically with a global distribution and occupy diverse niches primarily in tropical rainforests, contributing to over one-fifth of the biodiversity in some rainforests (Küper et al, 2004;Huang et al, 2008;Zhang et al, 2015;Givnish et al, 2016;Dewi et al, 2020). Most of the orchids occurring in forests are epiphytes (~20 000 species; ~19 000-21 000 according to different studies) and represent by far the largest group of epiphytic vascular plants (Zotz, 2013;Zotz et al, 2021;Fernández et al, 2023), providing an excellent model for the study of epiphytism.…”
Section: Introductionmentioning
confidence: 99%
“…Often this symbiosis is maintained into adulthood, although the OMF that provide for successful germination are not necessarily the same that associate with adult plants (Bayman et al 2016;Phillips et al 2020;Zhang et al 2018). While some OMF have a very broad distribution, on a local scale they are not ubiquitous so that local orchid populations may associate with different sets of fungi that may involve niche and/or spatial segregation (Fernández et al 2023;McCormick et al 2018;Swift et al 2019), although this is not always the case (Suarez et al 2016). The spatial distribution of the fungi may be dependent on biophysical factors which, in turn, would affect the distribution of their orchid symbionts (Izuddin et al 2019;Jacquemyn et al 2016).…”
Section: Introductionmentioning
confidence: 99%